Transport Properties of One-Dimensional van der Waals Heterostructures Based on Molybdenum Dichalcogenides - Daulet Sergeyev; Kuanyshbek Shunkeyev (Crystals)
The transport properties of one-dimensional van der Waals nanodevices composed of carbon nanotubes (CNTs), hexagonal boron nitride (hBN) nanotubes, and molybdenum dichalcogenide (MoX2) nanotubes were investigated within the framework of density functional theory (DFT). It was found that in nanodevices based on MoS2(24,24) and MoTe2(24,24), the effect of resonant tunneling is suppressed due to electron–phonon scattering. This suppression arises from the fact that these materials are semiconductors with an indirect band gap, where phonon participation is required to conserve momentum during transitions between the valence and conduction bands. In contrast, nanodevices incorporating MoSe2(24,24), which possesses a direct band gap, exhibit resonant tunneling, as quasiparticles can tunnel between the valence and conduction bands without a change in momentum. It was demonstrated that the presence of vacancy defects in the CNT segment significantly degrades quasiparticle transport compared to Stone–Wales (SW) defects. Furthermore, it was revealed that resonant interactions between SW defects in MoTe2(24,24)–hBN(27,27)–CNT(24,24) nanodevices can enhance the differential conductance under certain voltages. These findings may be beneficial for the design and development of nanoscale diodes, back nanodiodes, and tunneling nanodiodes.